Uso da realidade virtual e aumentada no ensino de segurança do trabalho na graduação - Fazinga, Wanessa Roberta; Lucena, Arthur Felipe Echs; Saffaro, Fernanda Aranha (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Technologies such as virtual reality and augmented reality are recognized by the construction industry as promising tools for visualization and simulation of the workplace. Regarding occupational safety education for undergraduate students, simulations and immersive experiences on the construction site can be useful resources to accomplish better understanding, especially concerning risk identification. This article aims to evaluate the acceptance and adaptation of civil engineering academic students in the use of virtual and augmented reality for the safety management of construction sites. An expository class of nine hours divided into three meetings was used to present concepts regarding virtual and augmented reality and their uses into the civil construction industry. Then, the students had to develop resources using these technologies to improve safety management in construction sites. Organized in groups, they presented their proposals to each other, experimenting with virtual and augmented reality mobile apps for various areas and activities on the construction site. Three proposals developed by the students were selected to be better detailed in this article. Analyzing these proposals, it was concluded that the students had improved their abilities to identify risks at the workplace, choose adequate personal protective equipment and develop strategies for training employees regarding safety practices.